Ontogeny of sexual size dimorphism in monitor lizards: males grow for a longer period, but not at a faster rate - Frynta, Daniel; Frýdlová, Petra; Hnízdo, Jan; Simková, Olga; Cikánová, Veronika; Velenský, Petr (Zoological science, 2010)
Monitor lizards belong to the largest and the most sexually dimorphic lizards in terms of size, making this group an ideal model for studies analyzing ontogenetic causes of sexual dimorphism. Understanding of these ontogenetic factors is essential to the current discussion concerning patterns of sexual dimorphism in animals. We examined the ontogenetic trajectories of body weight and snout-vent length to analyze the emergence of sexual size dimorphism. Experimental animals were 22 males and 13 females of mangrove-dwelling monitors (Varanus indicus) hatched at the Prague Zoo. They were regularly weighed and measured up to the age of 33-40 months, and subsequently sexed by ultrasonographic imaging. The logistic growth equation was used to describe and analyze the observed growth patterns. Our results confirm considerable sexual size dimorphism in the mangrove monitor. The mean asymptotic body weight of males was nearly three times higher than that of females. As the body size of male and female hatchlings is almost equal, and the growth rate parameter (K) of the logistic growth equation as well as the absolute growth rate up to the age of 12 months do not differ between the sexes, size differences between fully grown males and females should be attributed to timing of the postnatal growth. Males continue to grow several months after they reach the age when the growth of females is already reduced. Therefore, the sexual size dimorphism emerges and sharply increases at this period.
Keywords: stárnutí; zvířata; Animals; Female; Lizards; Body Size; ještěři; Male; Aging; ženské pohlaví; mužské pohlaví; pohlavní dimorfismus; velikost těla; Sex Characteristics